In Vitro Culture and Some Biochemical Characteristics of Fittonia albivenis (Lindl. ex Veitch) Brummitt - Belokurova, Valeriia; Lystvan, Kateryna; Volga, Dmytro; Vasylenko, Maksym; Kuchuk, Mykola (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
In this work we described a procedure of Fittonia albivenis (Lindl. ex Veitch) Brummitt in vitro conservation and microclonal propagation by enhanced bud proliferation from shoot tips as well as studying some biochemical characteristics of plants cultured both in vivo and in vitro. Multiple shoot formation from apical and axillary buds started in 4 months on MS/2 medium without growth regulators. Multiplication coefficients ranged from 6.0 ±1.9 to 14.7 ±2.6 for different plant clones. So, as a result of our work, the effective system of microclonal propagation of F.albiviens on hormone-free media was elaborated. It have been shown that application of plant growth regulators seems just to shorten the time period of Fittonia in vitro microclonal propagation but does not have any significant effect on multiplication coefficients. The total content of bioactive substances (flavonoids and phenolics) was about 0.2–0.45 % of dry weight, that is significantly less than its amount in known sources of polyphenols (e.g., ground coffee ). However, the data indicate the significant differences in the content of these bioactive substances between in vivo growing plants with dark-green (clone #1) and light-green leaves (clone #2) as well as different reactions to the transfer to the in vitro conditions. For some clones the significant increase in both phenolics and flavonoids amount was observed after such transfer. The clones with highest productivity have been identified and will be used in further researches.